Understanding the research advances on lumpy skin disease: A comprehensive literature review of experimental evidence - Liang, Zhengji; Yao, Kaishen; Wang, Shasha; Yin, Juanbin; Ma, Xiaoqin; Yin, Xiangping; Wang, Xiangwei; Sun, Yuefeng (Frontiers in Microbiology, 2022)
Lumpy skin disease (LSD) is caused by lumpy skin disease virus (LSDV), which can induce cattle with high fever and extensive nodules on the mucosa or the scarfskin, seriously influencing the cattle industry development and international import and export trade. Since 2013, the disease has spread rapidly and widely throughout the Russia and Asia. In the past few decades, progress has been made in the study of LSDV. It is mainly transmitted by blood-sucking insects, and various modes of transmission with distinct seasonality. Figuring out how the virus spreads will help eradicate LSDV at its source. In the event of an outbreak, selecting the most effective vaccine to block and eliminate the threat posed by LSDV in a timely manner is the main choice for farmers and authorities. At present, a variety of vaccines for LSDV have been developed. The available vaccine products vary in quality, protection rate, safety and side effects. Early detection of LSDV can help reduce the cost of disease. In addition, because LSDV has a huge genome, it is currently also used as a vaccine carrier, forming a new complex with other viral genes through homologous recombination. The vaccine prepared based on this can have a certain preventive effect on many kinds of diseases. Clinical detection of disease including nucleic acid and antigen level. Each method varies in convenience, accuracy, cost, time and complexity of equipment. This article reviews our current understanding of the mode of transmission of LSDV and advances in vaccine types and detection methods, providing a background for further research into various aspects of LSDV in the future.